Pendekatan Kreatif Produksi Iklan Layanan Masyarakat Bertema Anti Korupsi - Riyadi, Tunjung; Mahardhika, Satrya (Bina Nusantara University, 2011)
Corruption in Indonesia is such a life culture that is hardly to be eradicated. In order to solve it, there must be serious and strong will. Campaigning through public service advertising is one part of good moral message disseminating efforts. In producing PSA about corruption, it needs special strategy so the disseminated message could be transferred easily by target audience. One method is creative approach in advertising strategy. To make the production easier, there are stages: pre-production, production and post-production. Production method is through photographic and motion graphic. Motion graphic generally time-based visual media cutting which combine film language and graphic design. The result is a public service advertising film 60’ durated time, in anti-corruption theme. Meanwhile, disseminated message about close relationship between a mother and her child, unhappy because her child is a corruptor. Thus, audience will easily emotionally touched through this public service advertising.